A review of the participation of DDIT4 in the tumor immune microenvironment through inhibiting PI3K-Akt/mTOR pathway - Jiao, Yunshu; Xiang, Yang (Frontiers in Oncology, 2025)
DDIT4 (DNA Damage Inducible Transcript 4), a well-established inhibitor of the PI3K-Akt/mTOR pathway, is upregulated under cellular stress conditions. Extensive research has demonstrated that DDIT4 expression is aberrantly elevated in various malignancies, where it exhibits context-dependent roles in either tumor promotion or suppression. However, the mechanisms underlying how DDIT4 is involved in tumor immune regulation remain to be fully elucidated. This review systematically summarizes the multifaceted mechanisms by which DDIT4 participates in tumor immunomodulation, primarily through its inhibition of the PI3K-Akt/mTOR pathway to induce autophagy activation and metabolic reprogramming; furthermore, it comprehensively examines DDIT4’s regulatory effects on various components within the tumor immune microenvironment, including tumor cells, both innate and adaptive immune cells, and immunomodulatory cytokines. This comprehensive analysis aims to establish a theoretical foundation for considering DDIT4 as a potential therapeutic target in tumor immunotherapy.